2011
DOI: 10.1111/j.1447-0349.2010.00728.x
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a major in mental health nursing in Australian universities

Abstract: The difficulty recruiting and retaining an adequate mental health nursing workforce is acknowledged. The major in mental health nursing has been identified as a strategy to promote this specialist area of practice as desirable for students' future careers. Measuring its success requires the collection of detailed data about the structure, content, and uptake of these programmes. A survey was specifically developed to elicit descriptive information about the structure and content of a major in mental health nur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 24 publications
0
33
0
Order By: Relevance
“…It has been reported in the literature that the introduction of Bachelor Nursing programmes in Australia has created difficulties in recruiting sufficient graduates into mental health nursing. There is limited mental health nursing in undergraduate nursing programmes and few mental health nurse academics, therefore there is little incentive for undergraduate students studying nursing to consider mental health nursing as a career option . Some authors report that the students are discouraged from mental health nursing .…”
Section: Nursing Shortage: the Challenge For Mental Health Nursingmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported in the literature that the introduction of Bachelor Nursing programmes in Australia has created difficulties in recruiting sufficient graduates into mental health nursing. There is limited mental health nursing in undergraduate nursing programmes and few mental health nurse academics, therefore there is little incentive for undergraduate students studying nursing to consider mental health nursing as a career option . Some authors report that the students are discouraged from mental health nursing .…”
Section: Nursing Shortage: the Challenge For Mental Health Nursingmentioning
confidence: 99%
“…In nursing homes and general hospitals, AINs' work is focused on spending time with patients. In mental health nursing, the main focus of nursing is on direct patient contact, but because of the workloads, mental health nurses reported that it was difficult to find the time to spend with patients on inpatient units …”
Section: Mental Health Nursingmentioning
confidence: 99%
“…A major stream refers to the inclusion of additional theoretical and/or clinical learning in mental health nursing to enable nursing students to gain more experience in this specialist area, while still meeting the requirements as a comprehensively prepared nurse (Happell, Moxham, & Clarke, 2011;Kenny, McConnachie, Petrie, & Farrell, 2009;Mental Health Nurse Education Taskforce, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of major streams in mental health nurses was an initiative designed to provide students the opportunity to undertake additional theory and clinical experience in mental health if they elected to do so (Happell, Moxham, & Clarke, 2011;Kenny, McConnachie, Petrie, & Farrell, 2009;Mental Health Nurse Education Taskforce, 2008). However, the introduction of major streams in Australia was not accompanied by any guidelines defining the requirements and consequently, some majors included only minimal addition of theory and/or clinical content.…”
Section: Introductionmentioning
confidence: 99%